The Influence of Instagram Marketing Activities on Brand Equity of Beauty Products: A Customer Relationship Management (CRM) Approach - Kanaya, Aida Suni; Mariam, Siti; Sutawijaya, Ahmad Hidayat; Ramli, Abdul Haeba (Jurnal Logistik Indonesia, 2025)
This study aims to examine the influence of Instagram Marketing,Brand Awareness, Brand Image, Perceived QualitytoBrand Love, Brand Reuse IntentionAndBrand Trustto customersScarlett Whitening. The population in this study are customers whofollowInstagram accountScarlett Whiteningand have purchased and used the productScarlett Whiteningwith a minimum customer age of 18 years and domiciled in West Jakarta. The research sample consisted of 162 respondents. This research is a quantitative study using the SEM-PLS method. The results of the study indicate that Instagram Marketing has a positive effect onBrand Awareness, Instagram marketing has a positive impact onBrand Image, Instagram marketing has a positive impact onPerceived Quality,Brand Awarenesshave a positive influence onBrand Love, Brand Awarenesshave a positive influence onBrand Reuse Intention, Brand Awarenesshave a positive influence onBrand Trust, Brand Imagehave a positive influence onBrand Love, Brand Imagehave a positive influence onBrand Reuse Intention, Brand Imagehave a positive influence onBrand Trust, Perceived Qualityhave a positive influence onBrand Love, Perceived Qualityhave a positive influence onBrand Reuse Intentionand lastPerceived Qualityhave a positive influence onBrand Trust.